ANTIOXDATIVE ACTIVITIES OF WILD MACRO FUNGI GANODERMA APPLANATUM (PERS.) PAT. - K, NAGARAJ; MALLIKARJUN, N; NAIKA, RAJA; TM, VENUGOPAL (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The present research work was under taken to evaluate antioxidant activity and quantitative determination of phytoconstituents of various solvent extracts of wild macro fungi Ganoderma applanatum (Pers.) Pat. using in vitro models. The total phenolic content was estimated using Folin-Ciocalteu method and total flavonoid content was determined using aluminum chloride. In vitro antioxidant activity of solvent extracts were studied in different systems including DPPH scavenging assay, reducing power assay, metal chelating activity, superoxide radical assay and hydrogen peroxide activity along with standard. The results revealed that, the total phenolics and flavonoids were high and extracts showed good antioxidant capacity in DPPH radical scavenging assay compared to other in vitro models. The methanol extract can be considered as a valuable source of antioxidant products as the obtained values are more or less near to the used standard compounds. The present study concludes that methanolic extract of study species is effective in scavenging free radicals and has the potential to be powerful antioxidant. This potent antioxidant activity may be attributed to its high phenolic and flavonoid content. Â Keywords:Â Antioxidant activity, Ganoderma applanatum, Radical scavenging, Phenolics, flavonoids.